2001
DOI: 10.4049/jimmunol.167.5.2511
|View full text |Cite
|
Sign up to set email alerts
|

Expression of α4β7 Integrin Defines a Distinct Pathway of Lymphoid Progenitors Committed to T Cells, Fetal Intestinal Lymphotoxin Producer, NK, and Dendritic Cells

Abstract: During embryogenesis, the Peyer’s patch anlagen are induced by a cell population that produces lymphotoxin (LT) α1β2 following stimulation of IL-7Rα. In this study, we show that the LT-producing cell is localized within the IL-7Rα+ and integrin α4β7 (α4β7)+ population in the embryonic intestine. Lineage commitment to the LT producer phenotype in the fetal liver coincides with expression of α4β7. Before expression of α4β7, the potential of IL-7Rα+ population to generate B cells is lost. However, the progenitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
109
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(114 citation statements)
references
References 57 publications
(69 reference statements)
5
109
0
Order By: Relevance
“…Studies on PP development have led to a model whereby a hemopoietic "inducer" cell displays surface LT in response to IL-7 signaling. The LT-positive cell triggers LT␤R-positive mesenchymal cells to become a VCAM ϩ /ICAM ϩ "organizer" (4,13,25). The genetic lack of LT blocks PP development at the earliest detectable stage, i.e., formation of the VCAM/ICAM ϩ anlage at E16; however, it has not been formally proven that a hemopoietic cell delivers this LT signal at the early stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on PP development have led to a model whereby a hemopoietic "inducer" cell displays surface LT in response to IL-7 signaling. The LT-positive cell triggers LT␤R-positive mesenchymal cells to become a VCAM ϩ /ICAM ϩ "organizer" (4,13,25). The genetic lack of LT blocks PP development at the earliest detectable stage, i.e., formation of the VCAM/ICAM ϩ anlage at E16; however, it has not been formally proven that a hemopoietic cell delivers this LT signal at the early stages.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic lack of LT blocks PP development at the earliest detectable stage, i.e., formation of the VCAM/ICAM ϩ anlage at E16; however, it has not been formally proven that a hemopoietic cell delivers this LT signal at the early stages. Clearly, the Ikaros mouse reveals the need for hemopoietic cells in general and Ikaros null mice lack the critical IL-7R ϩ CD4 ϩ/Ϫ CD3 Ϫ LT ϩ cell that populates the rudimentary gut and mesenteric LN (22,25,26). It is certainly reasonable that the LT signal is delivered by a hemopoietic cell since expression in the adult appears to be limited to lymphoid cells and specifically to activated T, B, and NK cells and a subset of resting B cells (10,19,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, expression of the IL-7R a-chain (IL-7Ra) enables us to identify LTi progenitors in lineage marker-negative (Lin 2 ) populations (10,11). In addition, coexpression of a4b7integrin (a4b7) with IL-7Ra in CD4 + CD3 2 cells at neonatal LN suggested that a4b7 is another marker useful for defining LTi cells (8,12,13 (14). In addition, by employing an in vitro culture system, Lin 2 a4b7 2 IL-7Ra + fetal liver population, in which B-lymphoid potential is also retained, was shown to give rise to a4b7 + IL-7Ra + cells that lacked B-lymphoid potential (13).…”
mentioning
confidence: 99%
“…The absence of PP and LN in these mice cannot be restored by LT/LT␤R-dependent events later in life (10,11). The cellular source of LT required for the formation of PP and LN is believed to be a bone marrow-derived, CD4 ϩ , CD3 Ϫ , non-T and non-B lymphocyte precursor, which can be a progenitor of NK cells and dendritic cells (12)(13)(14). These requirements for gestational-dependent, LT/LT␤R-dependent events appear to be universal for the formation of secondary lymphoid structures, although the formation of cervical LN and MLN in the absence of these signals has been reported (15).…”
mentioning
confidence: 99%